'Your Chitumbuka is Shallow. It's not the Real Chitumbuka': Linguistic Purism Among Chitumbuka Speakers in Malawi (Nordic Journal of African Studies, 2004)
The paper discusses linguistic purism with reference to speakers of Chitumbuka in Malawi. Chitumbuka, along with other Malawian languages (except Chichewa/Chinyanja), was marginalised by the dictatorial regime of President Banda (1964-1994). One of the fruits of the post-Banda political dispensation has been the freedom to form language and cultural associations - and the Chitumbuka Language and Culture Association (CLACA) is one example. One of CLACA's self-given responsibilities is that of a language guardian. In keeping with this role, CLACA has made a number of pronouncements aimed at determining, for example, what the "real" Chitumbuka is; who the "genuine" speakers of Chitumbuka are; and what culturally corrosive issues should be excluded from Chitumbuka-medium textbooks; and so on. All these concerns boil down to the fear of loss of Chitumbuka's purity and/or the fear of Tumbuka cultural erosion. This paper points to the futility of attempts to keep language and culture pure.